Barriers and opportunities for the youth engagement in agribusiness: empirical evidence from Zambia and Vietnam. Issue 5 (4th July 2021) - Mulema, Joseph; Mugambi, Idah; Kansiime, Monica; Chan, Hong Twu; Chimalizeni, Michael; Pham, Thi Xuan; Oduor, George
ABSTRACT : We assessed barriers and opportunities for youth engagement in agribusiness. Results show that the majority of youth were engaged in agricultural production, especially in Zambia, while in Vietnam, they engaged in more diversified agricultural activities including input supply, transportation and advisory services delivery. Perceptions regarding the agricultural sector showed significant ( P  < 0.01) negative impact on youth participation in agribusiness in Vietnam, but not in Zambia. Barriers to effective youth engagement were; lack of start-up capital, low profitability of enterprises, and personal aspirations. Employing innovative value chain financing and market linkages can enhance enterprise profitability and youth participation in agribusiness.